2013
DOI: 10.1111/1744-9987.12100
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Decrease in CYP1A2 Function in Patients With End‐Stage Renal Disease

Abstract: Propranolol, the substrate of cytochrome P450 (CYP) 1A2 and CYP2D6, has been reported to be in high concentrations in end-stage renal disease (ESRD) patients. This has been thought to be due to the decrease in the nonrenal clearance of propranolol. The objective of this study is to elucidate the reason for the decrease in nonrenal clearance in ESRD patients. CYP1A2 and CYP2D6 activities were estimated by the phenacetin O-deethylation and methoprolol O-demethylation methods, respectively. Pooled normal serum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In experimental animal models of CKD, hepatic activity and expression levels of Cyp2d enzyme were unchanged, while those of Cyp3a family enzymes decreased. 5 Direct inhibition of CYP2D6-and CYP3A4/5-mediated microsomal metabolism was not observed after coincubation with 10% uremic serum or four uremic toxins, 22,23 while coincubation with uremic serum for 4 days decreased CYP3A4 activity in LS 180 cells (unfortunately, they did not examine the coincubation effect on CYP2D6). There are clear needs for further mechanistic studies examining elimination-route dependencies in the effect of CKD on nonrenal eliminations, and we hope that the in vivo observation in the current study will stimulate such efforts.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental animal models of CKD, hepatic activity and expression levels of Cyp2d enzyme were unchanged, while those of Cyp3a family enzymes decreased. 5 Direct inhibition of CYP2D6-and CYP3A4/5-mediated microsomal metabolism was not observed after coincubation with 10% uremic serum or four uremic toxins, 22,23 while coincubation with uremic serum for 4 days decreased CYP3A4 activity in LS 180 cells (unfortunately, they did not examine the coincubation effect on CYP2D6). There are clear needs for further mechanistic studies examining elimination-route dependencies in the effect of CKD on nonrenal eliminations, and we hope that the in vivo observation in the current study will stimulate such efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota-derived uremic toxins also affect CYP1A activity and expression [46,55,5860], with idole-3-acetic acid and indoxyl sulfate being the most potent. Indole-3-acetic acid decreases CYP1A2 activity by 50% in human microsomes [60].…”
Section: Phase I Metabolic Pathwaysmentioning
confidence: 99%
“…Indole-3-acetic acid decreases CYP1A2 activity by 50% in human microsomes [60]. A combination of hippuric acid, indoxyl sulfate and p-cresol also inhibit CYP1A2 activity in human microsomes [46].…”
Section: Phase I Metabolic Pathwaysmentioning
confidence: 99%
“…The effect of RI on such compounds is likely due to changes in DME expression, activity, protein binding, or a combination of these factors. Uremic toxins, compounds which accumulate in RI due to their decreased clearance, have been shown to alter DME expression and inhibit their activity [12,13,14,15,16]. These toxins may also affect the protein binding of drugs by competing for binding with proteins [17,18,24].…”
Section: Discussionmentioning
confidence: 99%
“…UGTs represent a major Phase II metabolic pathway, responsible for the glucuronidation of compounds [11]. It has been demonstrated that the expression and activity of these enzymes can be altered in RI, or in the presence of uremic toxins which are present at elevated levels in RI populations [12,13,14,15,16]. Furthermore, the alteration of protein binding of compounds may also alter metabolic clearance of compounds [3,17,18].…”
Section: Introductionmentioning
confidence: 99%